Digital Revolution and Cyber Threats as Its Consequence - Michał ZIMOŃ; Rafał KASPRZYK (Communications of International Proceedings, 2021)
The world is currently facing a digital revolution, characterized by rapid technical advancements and widespread digitalization. The evolution of the Internet contributed to the emergence of the information society. The possibilities that this revolution brings are intended to make people’s lives easier and to increase their standard of living. It turns out that, in addition to the benefits, there are cyber threats that appear at the same time. This requires constant monitoring and reaction, and in order to do so as efficiently as possible, it is vital to understand how the IT sector has evolved and predict where it may go next. Because of the dynamism of development, it is vital to keep up with changes in the industry, because existing solutions might soon become obsolete or alter sufficiently that a new approach to the issue is required.
Keywords: cybersecurity; cybercrime; malware; social engineering